Bakti Sosial dan Edukasi Masyarakat Terdampak Covid-19 di Kelurahan Pasir Kidul, Kecamatan Purwokerto Barat, Kabupaten Banyumas - Huda, Ulul; Haryanto, Budiman Setyo; Haryanto, Tenang (Solidaritas: Jurnal Pengabdian, 2022)
The Covid-19 pandemic has had a broad impact on people worldwide, including Pasir Kidul Village, Purwokerto District, Banyumas. Community Service is conducted in two main activities: social service and community education. Social service activities are implemented by providing essential food subsidies to insufficient people affected by Covid-19, distributing masks, and spraying disinfectant liquid in the mosque area, public space, and the homes of residents of Pasir Kidul Village. Community education activities were held in four sessions with the following materials: Islamic understanding of Covid-19; Understanding of praying law in congregation during the Covid-19 pandemic; Understanding of health protocols related to the implementation of worship during the Covid-19 pandemic; and Materials regarding the burial of Covid-19 corpses. The activity results show that residents feel supported and have a good understanding of the practice of worship during the pandemic. Community service is a solution to real problems in the community who want to carry out various activities and worship activities without worrying about contracting the coronavirus.